Near-infrared emission from Pr-doped borophosphate glass for broadband telecommunication - Sheng, Qiuchun; Wang, Xiaolin; Chen, Danping (Journal of luminescence, 2013)
Broadband near-infrared emission from Pr-doped borophosphate glass was investigated. The emission band had three peaks centered at ∼1040, 1163, and 1470nm with full widths at half maximum of 108, 147, and 205nm, respectively. These figures cover the entire spectrum of fiber-optic communication bands. The emission lifetimes at 1040, 1163, and 1470nm were 68, 321, and 68μs respectively. The product στ of stimulated emission cross-section (σ) and lifetime (τ) was 3.44×10−23cm2s. These results indicate that the Pr-doped glass can be used as an amplification medium for tunable lasers and broadband optical amplifiers for wavelength division multiplexing transmission system applications. ► Broadband near-infrared emission from Pr-doped PBAY glass was investigated. ► Mechanism of Pr3+ luminescence was discussed. ► The infrared emissions were ascribed to the 3P0→1G4, 1G4→3H5, and 1D2→1G4 transitions of Pr3+ ions. ► The στ product of Pr3+ in the PBAY glass was calculated to be 3.44×10−23cm2s.